‘Everyone can imagine their own Gellert’: the democratic artist and ‘inclusion’ in primary and nursery classrooms - Thomson, Pat; Hall, Christine (Taylor & Francis, 2015)
What do artists do when they work in schools? Can teachers do the same? These were the questions at the heart of our recent research, investigating the work of 12 artists working in primary and secondary schools in England. Funded by Creativity, Culture and Education as a ‘legacy’ project of Creative Partnerships (2003–2011) our intention was to develop a theorisation of artists’ practice that could inform the work that teachers do. In this paper, we report on a key aspect of the Signature Pedagogies project (www.signaturepedagogies.org.uk) the way in which artists approached the issue of inclusion. Through an examination of the work of three story-makers in primary and nursery schools, documented through observation, film and interview, we show that the democratic participatory practices they adopted were based on a fundamental belief that: every child was capable of having ideas; every child could contribute meaningfully to discussions; and every child was integral to a collective ‘performance’. We conclude that these artists’ democratic orientations may well be difficult for teachers to adopt in the current moment, but that this artistic work in schools may still provide a welcome relief for all involved, as well as maintaining an exemplar of alternative pedagogical practice that might be expanded in a changed policy environment.